A population-based, multifaceted strategy to implement antenatal corticosteroid treatment versus standard care for the reduction of neonatal mortality due to preterm birth in low-income and middle-income countries: the ACT cluster-randomised trial. Issue 9968 (14th February 2015) - Althabe, Fernando; Belizán, José M; McClure, Elizabeth M; Hemingway-Foday, Jennifer; Berrueta, Mabel; Mazzoni, Agustina; Ciganda, Alvaro; Goudar, Shivaprasad S; Kodkany, Bhalachandra S; Mahantshetti, Niranjana S; Dhaded, Sangappa M; Katageri, Geetanjali M; et al.
Summary: Background: Antenatal corticosteroids for pregnant women at risk of preterm birth are among the most effective hospital-based interventions to reduce neonatal mortality. We aimed to assess the feasibility, effectiveness, and safety of a multifaceted intervention designed to increase the use of antenatal corticosteroids at all levels of health care in low-income and middle-income countries. Methods: In this 18-month, cluster-randomised trial, we randomly assigned (1:1) rural and semi-urban clusters within six countries (Argentina, Guatemala, India, Kenya, Pakistan, and Zambia) to standard care or a multifaceted intervention including components to improve identification of women at risk of preterm birth and to facilitate appropriate use of antenatal corticosteroids. The primary outcome was 28-day neonatal mortality among infants less than the 5th percentile for birthweight (a proxy for preterm birth) across the clusters. Use of antenatal corticosteroids and suspected maternal infection were additional main outcomes. This trial is registered withClinicalTrials.gov, numberNCT01084096 . Findings: The ACT trial took place between October, 2011, and March, 2014 (start dates varied by site). 51 intervention clusters with 47 394 livebirths (2520 [5%] less than 5th percentile for birthweight) and 50 control clusters with 50 743 livebirths (2258 [4%] less than 5th percentile) completed follow-up. 1052 (45%) of 2327 women in intervention clusters who delivered less-than-5th-percentile infants received antenatal corticosteroids, compared with 215 (10%) of 2062 in control clusters (p<0·0001). Among the less-than-5th-percentile infants, 28-day neonatal mortality was 225 per 1000 livebirths for the intervention group and 232 per 1000 livebirths for the control group (relative risk [RR] 0·96, 95% CI 0·87–1·06, p=0·65) and suspected maternal infection was reported in 236 (10%) of 2361 women in the intervention group and 133 (6%) of 2094 in the control group (odds ratio [OR] 1·67, 1·33–2·09, p<0·0001). Among the whole population, 28-day neonatal mortality was 27·4 per 1000 livebirths for the intervention group and 23·9 per 1000 livebirths for the control group (RR 1·12, 1·02–1·22, p=0·0127) and suspected maternal infection was reported in 1207 (3%) of 48 219 women in the intervention group and 867 (2%) of 51 523 in the control group (OR 1·45, 1·33–1·58, p<0·0001). Interpretation: Despite increased use of antenatal corticosteroids in low-birthweight infants in the intervention groups, neonatal mortality did not decrease in this group, and increased in the population overall. For every 1000 women exposed to this strategy, an excess of 3·5 neonatal deaths occurred, and the risk of maternal infection seems to have been increased. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development.